Global engineering services: Shedding light on network capabilities. Issue 1 (21st March 2016) - Zhang, Yufeng; Gregory, Mike; Neely, Andy
Abstract: This paper addresses the operations challenges of effectively managing professional services on a global scale. The specific context for the study is professional engineering services and particularly those that are delivered globally – global engineering services (GES). Estimates suggest that the market for GES was around US930 billion in 2012, rising to US1.4 trillion by 2020 (ISG, 2013). Yet this influential sector receives scant attention in the operations management literature. The paper draws on six case studies to explore the operations management challenges of delivering GES. In doing so the paper introduces the concept of network capabilities for GES, highlighting the centrality that: (i) network resources – accessing and deploying dispersed resources, (ii) network coordination – coordinating and integrating network activities, and (iii) network learning – collective learning and knowledge management, all play in enabling the successful operational management of GES.